Study on energy saving strategy and Nash equilibrium of base station in cognitive radio network - Xiao-tong MA; Shun-fu JIN; Jian-ping LIU; Zhan-qiang HUO (Tongxin xuebao)
Spectrum utilization can be improved in cognitive radio network (CRN), however, the problem of increasing communication energy consumption was also brought. Under the premise of ensuring the experience quality of system users, the concept of green communication in CRN was introduced, and a novel energy saving strategy for base station was proposed. Accordingly, a two-dimensional discrete time Markov stochastic model with preemptive priority service and single working vacation was established. Using the method of a matrix geometric solution, the system performance of the energy saving strategy was evaluated in terms of energy saving rate, channel utilization, average delay of secon-dary users and interruption of secondary users. The theoretical analysis results and the simulation results verify the effec-tiveness of the energy saving strategy. From the perspective of economics, a profit function was constructed and a nonlinear optimization algorithm was designed to investigate the Nash equilibrium and the socially optimal behavior of the secondary user packets, then a pricing policy of licensed spectrum for secondary users was formulated. In view of different system parameters, the system experiment was carried out to validate the rationality of the pricing policy.